A TLD study of Acuros XB for lung SBRT using lung substitute material. - Soh, Roger Cai Xiang. (2013)
Purpose: The recent development of a new photon transport algorithm, Acuros XB, has shown good potential to be an alternative to the benchmark, Monte Carlo method. The advantage of Acuros XB (AXB) is in regions of significant heterogeneity where it has been shown to be almost equivalent to Monte Carlo and generally better than other advanced model-‐based algorithms. This project focuses on the use of Thermoluminesence Dosimeters (TLDs) for the validation of AXB on Lung SBRT. A comparison between AXB, AAA (Anisotropic Analytical Algorithm, Varian Medical Systems, USA), and physical TLD measurements in a lung substitute material (composition cork) will be studied. Methods: A thorough study was first done to prepare and calibrate TLDs for measurement. Next, a study of clinical cases was done to determine the treatment parameters and phantom dimensions for Lung Stereotactic Body Radiation Therapy (SBRT) cases. Two multilayered slab phantom, consisting of combinations of Plastic WaterTM (CIRS, Norfolk, VA) and composition cork was then built for TLD measurement. A corresponding virtual phantom was created in the clinical treatment planning system. Presence of bone is not considered in this study. The phantom dose distributions of field sizes 2x2, 5x5, and 10x10 cm2 for 6 MV photon beams were then analysed by comparison of TLD measurements on the phantom against AXB and AAA calculations on the virtual phantom. 2 Results: TLDs were carefully calibrated and the best linear dose response range was found to be between 0.1-‐1.0 Gy. All Lung SBRT treatments were delivered at 6MV with field sizes ranging from 5x5 to 10x10 cm2. 2x2 cm2 field size was included to study small stereotactic field effects in lung medium. Overall TLD results show that AXB was better than AAA in the lung medium and the lung to tissue interfaces. Conclusion: AXB was found to be an accurate algorithm for lung correction. Based on TLD measurements, it is accurate for AXB dose calculation in Lung SBRT, on areas where smaller field sizes (< 10x10 cm2) are normally used. Keywords: Acuros, TLD, Lung SBRT, composition cork